Successful Treatment of Pyogenic Liver Abscess Caused by Klebsiella Pneumoniae Using Antibiotics Alone: A Case Report - Liang W; Yang Q; Cai Y (Infection and Drug Resistance)
Wenxin Liang,* Qiansu Yang,* Yun Cai Center of Medicine Clinical Research, Department of Pharmacy, Medical Supplies Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun Cai, Center of Medicine Clinical Research, Department of Pharmacy, Medical Supplies Center of Chinese PLA General Hospital, 28 Fu Xing Road, Beijing, 100853, People’s Republic of China, Tel +86-10-6693-7166, Email caicai_hh@126.comAbstract: Liver abscess (LA), particularly pyogenic liver abscess (PLA) is a prevalent infectious disease of the digestive system in clinics. Some patients with PLA exhibit non-specific symptoms and signs, increasing the risk of missed and misdiagnoses. We report a case of a life-threatening PLA caused by Klebsiella pneumoniae, which was initially overlooked at presentation. A previously healthy male, one of the authors of this paper, presented with unexplained fever. Chest CT showed no pulmonary abnormalities, but the low-density shadow in the right lobe of the liver was not given sufficient attention. Based on local epidemiological trends of respiratory infections at that time, the patient was diagnosed with a respiratory infection and treated with oral levofloxacin. Later, due to uncontrollable disease progression and recurrent fever, the patient was hospitalized. MRI revealed an LA in the right lobe, and next-generation sequencing (NGS), tissue culture, and blood culture all indicated an infection with K. pneumoniae. Despite unsuccessful drainage, the patient received 22 days of intravenous anti-infective treatment with meropenem, levofloxacin, and cefoperazone/sulbactam. His condition improved and he was subsequently discharged. After discharge, the patient continued oral treatment with levofloxacin and cefuroxime axetil for another 21 days until the abscess completely disappeared. The PLA took a total of 48 d from detection to complete resolution.Keywords: liver abscess, pyogenic liver abscess, Klebsiella pneumoniae, antibiotics